Preparation and purification of an immunoregulatory peptide from Stolephorus chinensis of the East Sea of China. (November 2020) - Xu, Baogui; Ye, Lei; Tang, Yunping; Zheng, Jiawen; Tian, Xiaoxiao; Yang, Yuxia; Yang, Zuisu
Graphical abstract: Highlights: An immunomodulatory peptide was isolated from Stolephorus chinensis . The amino acid sequence of immunomodulatory peptide was identified as Tyr-Val-Met-Arg-Phe. Fraction with molecular weight of < 1 kDa showed maximum RPR toward RAW 264.7 cells (70.03 %). Abstract: Immunomodulatory peptides derived from marine organisms are potential sources of new immunomodulating drugs. This study aimed to investigate the optimal enzymatic hydrolysis conditions of immunoregulatory peptides from Stolephorus chinensis . The relative proliferation rate (RPR) of RAW264.7 macrophages was set as the screening index. The immunoregulatory peptides from S. chinensis was prepared via process optimization, ultrafiltration, ion-exchange chromatography, and reverse-phase high-performance liquid chromatography (RP-HLPC). The amino acid sequence of the immunoregulatory peptide from S. chinensis (IPSC) was identified to be Tyr-Val-Met-Arg-Phe (YVMRF; MW 715.4 Da) using Edman degradation and mass spectrometry. In addition, the macrophages became larger with more pseudopods after IPSC treatment, indictating that IPSC stimulated RAW 264.7 differentiation. IPSC also increased productions of nitric oxide (NO), interleukin-6 (IL-6), interleukin-1β (IL-1β), and tumor necrosis factor-α (TNF-α). Our results provide a theoretical basis for preparing immunomodulatory functional food from S. chinensis in future.